Superior Potassium Ion Storage via Vertical MoS2 "Nano‐Rose" with Expanded Interlayers on Graphene. Issue 42 (22nd September 2017) - Xie, Keyu; Yuan, Kai; Li, Xin; Lu, Wei; Shen, Chao; Liang, Chenglu; Vajtai, Robert; Ajayan, Pulickel; Wei, Bingqing
Abstract: Potassium has its unique advantages over lithium or sodium as a charge carrier in rechargeable batteries. However, progresses in K‐ion battery (KIB) chemistry have so far been hindered by lacking suitable electrode materials to host the relatively large K + ions compared to its Li + and Na + counterparts. Herein, molybdenum disulfide (MoS2 ) "roses" grown on reduced graphene oxide sheets (MoS2 @rGO) are synthesized via a two‐step solvothermal route. The as‐synthesized MoS2 @rGO composite, with expanded interlayer spacing of MoS2, chemically bonded between MoS2 and rGO, and a unique nano‐architecture, displays the one of the best electrochemical performances to date as an anode material for nonaqueous KIBs. More importantly, a combined K + storage mechanism of intercalation and conversion reaction is also revealed. The findings presented indicate the enormous potential of layered metal dichalcogenides as advanced electrode materials for high‐performance KIBs and also provide new insights and understanding of K + storage mechanism. Abstract : The synthesis of MoS2 roses grown upward on reduced graphene oxide sheet (MoS2 @rGO) is demonstrated via a two‐step solvothermal route. By rational material and structure design, the MoS2 @rGO composite exhibits several fascinating characteristics for battery applications. When serving as the anode material for K–ion batteries (KIBs), the MoS2 @rGO composite exhibits one of the best electrochemical performances for KIBs to date.